Penggunaan Video Ajar Youtube untuk Mengoptimalkan Interaksi Belajar Siswa Kelas VII MTsN 2 Kota Blitar - Naila Alfiatur Rohmah; Yudi Krisno Wicaksono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the use of YouTube-based instructional videos in optimizing students' learning interaction on Sociology material in Social Studies learning for Grade VII at MTsN 2 Kota Blitar. The research employed a qualitative approach with a case study design. The subjects consisted of a Social Studies teacher and seventh-grade students involved in the learning process using instructional videos. Data were collected through observation, interviews, and documentation. The findings show that the use of YouTube-based instructional videos enhances students' attention, participation, and engagement in the learning process. Visually engaging and relevant videos help students become more active in discussions, asking questions, and responding to the lesson. Teachers also find it easier to connect the material with real-life contexts through the visualizations provided by the videos. Although challenges such as limited internet access and infrastructure issues were encountered, they were addressed through careful planning. In conclusion, the use of YouTube-based instructional videos proves effective in optimizing students’ learning interaction and provides a more meaningful and enjoyable learning experience.